Addition of a theory of financial globalization in context of expansion of foreign bank capital - Кузьмук, Ігор Ярославович (Technology audit and production reserves, 2014)
The paper considers the essence of financial globalization and its effects for the country’s economic development, in particular the market. The essence of financial markets was studied, current trends were analyzed and factors influencing the formation of the Ukrainian market were determined. Special attention was paid to the expansion of foreign bank capital as a key factor in the development of financial globalization, potential advantages and disadvantages of this process were analyzed. It was proved that these advantages and disadvantages cannot serve as a universal model to analyze the effects of foreign banks expansion as the main motive of the output of banking structures beyond national markets is a desire to make a profit, and some advantages and disadvantages occur as a consequence of selecting the individual strategy by each bank structure. The necessity of a comprehensive government regulation of the financial market, in the context of opening, operation and liquidation of the sirloin and representative offices of foreign banks for maximizing the beneficial effects of their activities and leveling of potentially negative consequences.